Feasibility of the application of the CarbFix method to geothermal power plants globally - Agla Sól Pétursdóttir 1996- (2021)
Although geothermal energy is considered to be renewable energy, it still emits some amount of polluting gases to the atmosphere. CarbFix is a method where carbon dioxide and hydrogen sulfide are injected into the subsurface, where it has the potential of mineralizing within two years. CarbFix has been in operation since 2014 and is located at Hellisheiði, a geothermal power plant in Iceland. By applying this method emissions to the atmosphere are reduced. This feasibility presented in this study maps out to which extent the CarbFix method could be applied to other geothermal power plants in the ten countries with the highest electricity production from geothermal energy. The feasibility depends on the rock type where the power plants are located, the amount of carbon dioxide emissions from the power plants, and the condenser design for the power plant. To determine potentially feasible locations, the CarbFix Mineral Storage Atlas was used. Carbon dioxide emissions data for geothermal power plants were very limited, and there was limited availability of information about the detailed design of the condenser in the power plant. Based on the results, most geothermal power plants were not feasible due to the power plant's location or because of the power plant using a direct contact condenser. There was no feasibility with the current method for the plants in the Philippines, Turkey, or Italy because the power plants were not located in geology with feasible rock types. However, there were geothermal power plants feasible in the United States, Indonesia, Iceland, Kenya, New Zealand, and Japan. Although there were limitations to the data gathered, this study now holds information on the CO2 emissions and condenser design for many geothermal power plants around the world. Þrátt fyrir að jarðvarmaorka sé endurnýjanleg orka þá gefur hún samt frá sér nokkuð af mengandi lofttegundum í andrúmsloftið. CarbFix er aðferð þar sem koldíoxíð og brennisteinsvetni er leyst upp í vatni og dælt niður í berg þar sem það myndar ...